Transformaciones de Datum (ING) - Ramírez, Manuel (2004)
With the generalized use of satellite techniques and their applications in land surveying and geodesy, a necessity to transform between global and local reference frames has been seen. In this article, a description and comparison of the most common methods for coordinate transformation between geodetic datums is given. Different approaches such as the seven parameter transformation (Bursa-Wolf method), multiple regression, and Molodensky’s transformation are explained among other. Fundamental transformation equations as well as MatLab code for their implementation is provided.